Detection of endogenous NPY release determined by novel GRAB sensor in cultured cortical neurons - Christensen, Emma Kragelund; Konomi-Pilkati, Ainoa; Rombach, Joscha; Comaposada-Baro, Raquel; Wang, Huan; Li, Yulong; Sørensen, Andreas Toft (Frontiers in Cellular Neuroscience, 2023)
Neuropeptide Y (NPY) is an abundantly expressed peptide in the nervous system. Its widespread distribution along with its receptors, both centrally and peripherally, indicates its broad functions in numerous biological processes. However, the low endogenous concentration and diffuse distribution of NPY make it challenging to study its actions and dynamics directly and comprehensively. Studies on the role of NPY have primarily been limited to exogenous application, transgene expression, or knock-out in biological systems, which are often combined with pharmacological probes to delineate the involvement of specific NPY receptors. Therefore, to better understand the function of NPY in time and space, direct visualization of the real-time dynamics of endogenous NPY is a valuable and desired tool. In this study, for the first time, we demonstrate and characterize the direct detection of endogenous released NPY from cultured cortical neurons using the first-generation and newly developed intensiometric green fluorescent G-protein-coupled NPY sensor (GRAB NPY1.0). A dose-dependent fluorescent signal was observed upon exogenous NPY application in nearly all recorded neurons. Pharmacologically evoked neuronal activity induced a significant increase in fluorescent signal in 32% of neurons, reflecting the release of NPY, despite only 3% of all neurons containing NPY. The remaining pool of neurons expressing the sensor were either non-responsive or displayed a notable decline in the fluorescent signal. Such decline in fluorescent signal was not rescued in cortical cultures transduced with an NPY overexpression vector, where 88% of the neurons were NPY-positive. Overexpression of NPY did, however, result in sensor signals that were more readily distinguishable. This may suggest that biological factors, such as subtle changes in intracellular pH, could interfere with the fluorescent signal, and thereby underestimate the release of endogenous NPY when using this new sensor in its present configuration. However, the development of next-generation NPY GRAB sensor technology is expected soon, and will eventually enable much-wanted studies on endogenous NPY release dynamics in both cultured and intact biological systems.